2002
DOI: 10.1111/j.1748-0361.2002.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

An Outreach Intervention for Older Rural African Americans

Abstract: This article describes the process, approaches, and selected outcomes of a rural care management outreach intervention for older African Americans in South Carolina. The model is a community-academic partnership between a federally qualified community health center, a rural health clinic, and the Medical University of South Carolina. Its aim is to improve access to and utilization of health care and social services to enhance the quality of life of older African Americans. This is being accomplished by using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…Research has demonstrated the effectiveness of community health workers in several areas relevant to the needs of rural seniors: hypertension control (Krieger et al, 1999); appointment keeping; continuity of care (Brownstein et al, 2005); development of a ''therapeutic alliance'' between patient, provider, and family=community support systems; risk reduction; improving patterns of health care utilization (Nemcek & Sabatier, 2003); diabetes control (Norris et al, 2006;Krieger et al, 1999); increasing the use of preventive services; keeping appointments; increasing adherence to recommended regimens; promoting appropriate use of health services (Witmer, Sarena, Finnocchio, Leslie, & O'Neil, 1995); and linking older clients to social services (Forti & Koerber, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated the effectiveness of community health workers in several areas relevant to the needs of rural seniors: hypertension control (Krieger et al, 1999); appointment keeping; continuity of care (Brownstein et al, 2005); development of a ''therapeutic alliance'' between patient, provider, and family=community support systems; risk reduction; improving patterns of health care utilization (Nemcek & Sabatier, 2003); diabetes control (Norris et al, 2006;Krieger et al, 1999); increasing the use of preventive services; keeping appointments; increasing adherence to recommended regimens; promoting appropriate use of health services (Witmer, Sarena, Finnocchio, Leslie, & O'Neil, 1995); and linking older clients to social services (Forti & Koerber, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the services they could provide to rural adults include conducting needs assessments to identify problems, delivering educational programs, making referrals, coordinating care plans and service delivery options, and conducting follow-up monitoring, education, and support. Researchers have found that paraprofessionals known as indigenous lay educators or lay health advisors (LHAs), have been effective in increasing access to healthcare services among minority, low-income older adults (Krieger, Collier, Song, & Martin, 1999); linking older clients to social services such as Medicaid and the Food Stamp Program; and educating older adults on how to manage financial resources (Forti & Koerber, 2002). While these recommendations broadly provide a framework for action, recommendations for what will work in specific rural communities can only come from the residents themselves.…”
Section: Strategies To Facilitate Aging In Place In Rural Communitiesmentioning
confidence: 99%
“…[3][4][5][6] Transportation is reported as one of the major concerns reported by rural residents in discussing limitations to their access to health care or their participation in health programs. [7][8][9][10] However, while the contribution of distance to utilization has been dissected in numerous studies, transportation is generally lumped with other explanatory variables in analyses of rural health care utilization. [11][12][13] Two areas in which access to transportation has received substantial attention are those of emergency medical services and the needs of older adults.…”
mentioning
confidence: 99%
“…While access to transportation for routine care has been ignored, access to transportation for emergency care in rural communities, whether on the ground or in the air, is a major theme for rural health. 14 The need for access to transportation for health care utilization among older adults in rural communities has been the focus of several studies and reviews, 7,8,13,[15][16][17][18][19][20] with the need to provide alternatives to the private automobile if older adults are to independently access care being a major theme.…”
mentioning
confidence: 99%
“…Access to health care services remains an ongoing problem and one which community health nurses must deal with on a day‐to‐day basis. No one in health care will dispute the relationship between the health of a population and its access to health care services (Byck, Walton, & Cooksey, 2002; Forti & Koerber, 2002; Rosswurm, 2001). The problem of access to health care services is often compounded in those rural areas that are remote and exist well outside urban boundaries where transportation is limited (Cox, 1997).…”
mentioning
confidence: 99%